The anti-obesity effects of Lactobacillus casei strain shirota versus orlistat on high fat diet-induced obese rats - Karimi, Golgis; Sabran, Mohd Redzwan; Jamaluddin, Rosita; Parvaneh, Kolsoom; Mohtarrudin, Norhafizah; Ahmad, Zuraini; Khazaai, Huzwah; Khodavandi, Alireza (Co-Action Publishing, 2015)
BACKGROUND:Obesity and overweight are major public health problems. Various factors, such as daily nutritional habits, physical inactivity, and genetic, are related to the prevalence of obesity. Recently, it was revealed that the gut microflora may also play an important role in weight management. Thus, this study aimed to determine the anti-obesity effects of Lactobacillus casei strain Shirota (LcS) compared with those of orlistat in an animal model fed a high-fat diet (HFD).